Muscle-dependent maturation of tendon cells is induced by post-transcriptional regulation of stripeA. - Volohonsky, G.; Edenfeld, G.; Klambt, C.; Volk, T. (Development, 2007)
Terminal differentiation of single cells selected from a group of equivalent precursors may be random, or may be regulated by external signals. In the Drosophila embryo, maturation of a single tendon cell from a field of competent precursors is triggered by muscle-dependent signaling. The transcription factor Stripe was reported to induce both the precursor cell phenotype, as well as the terminal differentiation of muscle-bound tendons. The mechanism by which Stripe activates these distinct differentiation programs remained unclear. Here, we demonstrate that each differentiation state is associated with a distinct Stripe isoform and that the Stripe isoforms direct different transcriptional outputs. Importantly, the transition to the mature differentiation state is triggered post-transcriptionally by enhanced production of the stripeA splice variant, which is typical of the tendon mature state. This elevation is mediated by the RNA-binding protein How(S), with levels sensitive to muscle-dependent signals. In how mutant embryos the expression of StripeA is significantly reduced, while overexpression of How(S) enhances StripeA protein as well as mRNA levels in embryos. Analysis of the expression of a stripeA minigene in S-2 cells suggests that this elevation may be due to enhanced splicing of stripeA. Consistently, stripeA mRNA is specifically reduced in embryos mutant for the splicing factor Crn, which physically interacts with How(S). Thus, we demonstrate a mechanism by which tendon cell terminal differentiation is maintained and reinforced by the approaching muscle.